Proposing a Methodological Borderland: Combining Chicana Feminist Theory With Transformative Mixed Methods Research. (April 2021) - Garcia, Gina A.; Ramirez, Jenesis J.
In this article, we propose a "methodological borderland, " defined as a methodological space in constant transition; one that allows researchers to combine multiple methods, data points, and theories, guided by a desire for social justice for studied populations. In doing so, we urge mixed methods researchers to access theoretical frameworks that are grounded in the ways of knowing of participants and that promote critical analysis and interpretation in conjunction with transformative mixed methods. Using a convergent mixed methods approach, we illustrate the way Chicana feminist theory can be used as a theoretical lens and analytic tool that can amplify the voices of Raza college students. We suggest and illustrate ways to use theory to enhance transformative mixed methods.